2008
DOI: 10.1021/ma800702f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polydispersity on the Self-Assembly Structure of Diblock Copolymers under Various Confined States: A Monte Carlo Study

Abstract: We studied the self-assembly of polydisperse diblock copolymers under various confined states by Monte Carlo simulation. When the copolymers were confined within two parallel walls, it was found that the ordered strip structures appeared alternately with the increase in wall width. Moreover, the wall width at which the ordered structure appeared tended to increase with an increase in the polydispersity index (PDI). On the other hand, the simulation results showed that the copolymers were likely to form ordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 49 publications
(96 reference statements)
1
35
0
Order By: Relevance
“…A flurry of theoretical [25][26][27][28][29][30][31][32][33][34] and a͒ Authors to whom correspondence should be addressed: Electronic addresses: hillmyer@umn.edu and bates@cems.umn.edu. experimental 11,27,[35][36][37][38][39][40][41][42][43] studies of polydispersity effects in AB block copolymers followed Bendejacq et al's report.…”
Section: Introductionmentioning
confidence: 99%
“…A flurry of theoretical [25][26][27][28][29][30][31][32][33][34] and a͒ Authors to whom correspondence should be addressed: Electronic addresses: hillmyer@umn.edu and bates@cems.umn.edu. experimental 11,27,[35][36][37][38][39][40][41][42][43] studies of polydispersity effects in AB block copolymers followed Bendejacq et al's report.…”
Section: Introductionmentioning
confidence: 99%
“…Some computational studies on self-assembly of block copolymer blends in solution have been reported in the last decade, including self-consistent-field theory (SCFT), 11,15,17,18 Monte Carlo, [19][20][21][22][23] Brownian Dynamics 24 and Dissipative Particle Dynamics. 16,[25][26][27][28][29][30][31][32][33] A number of publications focuses on block copolymer/homopolymer blends (AB/A and AB/C), 20,31,34 block copolymers in small amounts as compatibilizers for homopolymer blends (AB/A/B, AB/A/C or AB/C/D).…”
Section: Introductionmentioning
confidence: 99%
“…As far as blends of two block copolymers are concerned, few reports are available. Focus has been on AB/AB copolymers with different molecular weights 22,38 but less on AB/AC blends. AB/AC blends have been considered before, but only with similar molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…For the self-assembly of linear or star triblock copolymers in the confined pores, a series of morphological phase diagrams have been established using self-consistent field theory and simulated annealing method [16,[21][22][23]. Moreover, complex self-assembled structures can be generated by diblock copolymer mixtures under various confined conditions [24,25]. For example, morphological transitions from concentric cylindrical barrel structures to screw/cylinder structures and then to stacked disk/cylinder structures upon decreasing the pore diameter have been observed in the binary blends of A 15 B 7 and B 7 C 15 copolymers under cylindrical confinements.…”
Section: Introductionmentioning
confidence: 99%